PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN MAKANAN DAN MINUMAN - Ena, Nina Nura; Budiman, Judi (Jurnal Riset Ilmu Akuntansi, 2026)
The purpose of this study was to analyze the influence of profitability and liquidity on firm value, which are suspected to be factors in the revival of companies in the food and beverage subsector on the Indonesia Stock Exchange (IDX) after being hit by the COVID-19 pandemic (2021-2024). Of the 97 companies, 18 were selected as samples using a purposive sampling technique. Profitability was assessed using ROA, liquidity was measured using CR, and firm value was measured using PBV. This quantitative study, using 72 secondary data from financial reports, was tested using a multiple linear regression approach using SPSS. The results demonstrated that profitability had a significant positive effect on firm value, while liquidity had a negative but insignificant effect. Both profitability and liquidity significantly influenced firm value.